1986
DOI: 10.1111/j.2044-8260.1986.tb00667.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a self‐help manual for media‐recruited problem drinkers: Six‐month follow‐up results

Abstract: A total of 785 individuals responded to a newspaper advertisement offering free help to cut down drinking and were sent alternately either a self-help manual based on behavioural principles or a general information and advice booklet. Of these, 247 (31.3 per cent) returned assessment questionnaires or agreed to be interviewed by telephone and 132 of these respondents (53.4 per cent) were successfully contacted at six-month follow-up. Those lost to follow-up were more 'socially stable' on initial measures than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
3

Year Published

1989
1989
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(39 citation statements)
references
References 14 publications
1
35
3
Order By: Relevance
“…In particular, BI patients are the group that is most comparable with the studies in Bien et al's review. Our effect size of 0.72 for any drinking is larger than those of five studies that found statistical significance when BI was compared to a control group: Babor & Grant [22], Heather et al [23,27,29] and Daniels et al [26]. Finally, effect sizes for the studies for which pre-post changes in control-group outcomes were available, were consistently lower than SAMHSA's effect sizes.…”
Section: Comparisons With Results From Other Sbi Studiescontrasting
confidence: 45%
See 1 more Smart Citation
“…In particular, BI patients are the group that is most comparable with the studies in Bien et al's review. Our effect size of 0.72 for any drinking is larger than those of five studies that found statistical significance when BI was compared to a control group: Babor & Grant [22], Heather et al [23,27,29] and Daniels et al [26]. Finally, effect sizes for the studies for which pre-post changes in control-group outcomes were available, were consistently lower than SAMHSA's effect sizes.…”
Section: Comparisons With Results From Other Sbi Studiescontrasting
confidence: 45%
“…Standardized effect sizes from 14 of the studies reviewed by Bien et al [16] are given in Table 4 [ [22][23][24][25][26][27][28][29][30][31][32][33][34][35]. The within-group effects are described by the baseline to follow-up changes in alcohol use among patients receiving BI, and are thus similar in design to the standardized effect sizes from our analysis also given in Table 4.…”
Section: Comparisons With Results From Other Sbi Studiesmentioning
confidence: 68%
“…In addition, it is informative that those studies comparing bibliotherapy alone and bibliotherapy augmented by offered consultation (in person or by telephone) have often found no additive effect of consultation, perhaps in part because most bibliotherapy recipients decline the offer of further help. Nevertheless, bibliotherapy has been found to increase the seeking of formal treatment among heavier drinkers (Heather et al, 1986). One study reported an additive effect of an in-person motivational interview and assessment (Sanchez-Craig et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In the first of two Scottish studies, Heather, Whitton, and Robertson (1986) asked whether receiving a self-help manual alone (with no therapist contact) would be beneficial. They recruited problem drinkers through newspaper advertisements, and sent via mail either a self-help manual (based on behavioral principles) or an informational booklet (as a control group).…”
Section: Variations and Additions To Bibliotherapymentioning
confidence: 99%
“…(Gould & Clum, 1993, p. 170). They have been used for decades in areas as diverse as obesity (e.g., Balch & Ross, 1974), sexual dysfunction (Van Lenkveld, 1998), alcohol abuse (e.g., Heather, Whitton, & Robertson, 1986), and memory skills (Scogin, Storandt, & Lott, 1985). The present article is a meta-analysis of outcome studies on the efficacy of SATs for depression and anxiety in clinical populations.…”
mentioning
confidence: 99%